2015
DOI: 10.1007/s40268-015-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Imeglimin: A Potential New Multi-Target Drug for Type 2 Diabetes

Abstract: Imeglimin is a novel agent currently in development to treat type 2 diabetes. Laboratory studies have demonstrated that it has the potential to impact the three main pathophysiologic components of type 2 diabetes: impaired glucose uptake by muscle tissue, excess hepatic gluconeogenesis, and increased beta-cell apoptosis. Preliminary human studies that have been published within the last 2 years demonstrate that imeglimin improves hemoglobin A1c and fasting plasma glucose similarly when compared with metformin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 11 publications
0
30
0
3
Order By: Relevance
“…Imeglimin is an emerging as a novel glucose‐reducing agent. In diabetic rats, plasma glucose was reduced with imeglimin treatment (25, 50, and 100 mg/kg) in a similar manner to metformin (50 mg/kg; Fouqueray et al, ) and shown to target all three of the contributing physiologic defects in type 2 diabetes (Fouqueray et al, ; Vuylsteke, Chastain, Maggu, & Brown, ; Table ). Imeglimin (200 mg/kg, b.i.d.…”
Section: Major Mechanisms Of Action Of Imeglimin and Metformin To Redmentioning
confidence: 97%
“…Imeglimin is an emerging as a novel glucose‐reducing agent. In diabetic rats, plasma glucose was reduced with imeglimin treatment (25, 50, and 100 mg/kg) in a similar manner to metformin (50 mg/kg; Fouqueray et al, ) and shown to target all three of the contributing physiologic defects in type 2 diabetes (Fouqueray et al, ; Vuylsteke, Chastain, Maggu, & Brown, ; Table ). Imeglimin (200 mg/kg, b.i.d.…”
Section: Major Mechanisms Of Action Of Imeglimin and Metformin To Redmentioning
confidence: 97%
“…Imeglimin, with the chemical name of (6R)-(+)-4-dimethylamino-2-imino-6-methyl-1,2,5,6-tetrahydro-1,3,5-triazine hydrochloride, is a new promising antidiabetic medication which has demonstrated antihyperglycemic effects in various studies [8,11]. It is an inhibitor of the oxidative-phosphorylation process taking place inside the mitochondria of aerobic cells and thereby can exert potent metabolic effects in eukaryotic cells [12].…”
Section: Imegliminmentioning
confidence: 99%
“…Therefore, it has potential advantages to other oral hypoglycemic agents, which target only one or two defects and not all the three defects, namely, increased glycogenesis in the liver, impaired insulin secretion from the pancreas, and insulin resistance in muscles. Thereby, imeglimin is one of the potentially promising medications for managing patients with T2DM, if approved [8] (Table 1).…”
Section: Imegliminmentioning
confidence: 99%
See 2 more Smart Citations